A New Ilarvirus Found in French Hydrangea - Giuseppe Parrella; Elisa Troiano (Plants, 2022)
In this study, a new virus was identified in French hydrangea plants, exhibiting chlorotic vein banding and necrotic ring spots on older leaves. The virus was mechanically transmitted to herbaceous hosts, in which it induced local and systemic or only local symptoms. The genome of the new virus was characterized and consisted of three RNA sequences that were 3422 (RNA 1), 2905 (RNA 2) and 2299 (RNA 3) nucleotides long, with five predicted open reading frames; RNA2 was bicistronic and contained conserved domains and motifs typical of ilarviruses. The phylogenetic analysis of the predicted proteins—p1, p2a, p3a and p3b—revealed its close relationship to recognized members of subgroup 2 within the genus Ilarvirus. Homologous antiserum was effective in the detection of the virus in plant extracts and no cross reactions with two other distinct members of subgroup 2 were observed. Overall, the biological features, phylogenetic relationships and serological data suggest that this virus is a new member of the genus, for which we propose the name hydrangea vein banding virus (HdVBV).